Comparing the performance of the public and private leather and footwear sector in Algeria from the perspective of the production and exploitation accounts - Haichar Ahmed Tedjani; chekhaoui Abdelaziz (Journal of Excellence for Economics and Management Research, 2017)
We try to study the leather and footwear sector by examining the extent of statistical differences and the degree of significance of these differences in the studied variables between the private and public sectors. This research was carried out over a period of time from 1974 to 2007. Based on annual data related to totals, the values of the studied variables were calculated as percentages of private and public sector participation in each total.